Analysis of low-grade heat driven ethanol-silica gel adsorption chiller - Habash, Rami; Ilis, Gamze Gediz; Demir, Hasan; Öztop, Hakan Fehmi Fehmi (Elsevier, 2021)
The main objective of this study is to design a low-grade heat driven ethanol-silica gel adsorption chiller. The low-grade waste heat is utilized in an adsorption chiller. For this purpose, an innovative bed heat exchanger including a condenser embedded inside the adsorbent bed is uniquely designed. The silica gel/ethanol pair is examined both analytically and numerically in this article. The cycles of the adsorption chiller are performed experimentally. The obtained isotherm for the silica gel/ethanol fitted to Type III isotherm behavior. The obtained equations of isotherm are also validated numerically. The new adsorption chiller design used in this study has reduced the desorption temperature for silica gel/ethanol pair to 37 degrees C which will widen the application area of adsorption chillers. The COMSOL Multiphysics program is used for 2-D numerical analysis of adsorbent bed. The mass transfer inside of the particle, the heat transfer in porous media, and Darcy law are used for analyzing the heat and mass transfer of the bed. Temperature and concentration distributions of adsorbent bed during the duration of adsorption and desorption processes are examined numerically. The specific cooling power and volumetric cooling power values of the system are found as 20.2 Wkg1 and 4.5 kWm 3, respectively.
Keywords: Low-grade heat source; Silica gel; ethanol pair; Adsorption chiller; Combined condenser-bed design